Importancia de la correcta imputación del delito de robo, garantía de un adecuado proceso penal - Cuenca Jaramillo, Sergio Marcel; Vargas Lapo, Héctor Jefferson (Machala, 2020)
In order to analyze the importance of the correct imputation of the crime of theft for a proper criminal process, a descriptive research of a bibliographical review type was developed with a qualitative approach, based on the methods: historicallogical, exegetical and analytical-synthetic. Among the main findings are that a quality accusation is important for the proper development of the criminal process, which is evident in the legal configuration of the crime, the correct determination of responsibility and the exercise of due process guarantees in compliance with the principles of the criminal process. A proper imputation avoids extensive interpretations and that the crime is not mistakenly confused with robbery or fraud.
Con el objetivo de analizar la importancia de la correcta imputación del delito de robo para un adecuado proceso penal, se desarrolló una investigación descriptiva de tipo revisión bibliográfica con enfoque cualitativo, sustentada en los métodos: histórico-lógico, exegético y analítico–sintético. Entre los principales hallazgos se destacan que una imputación de calidad es importante para el desarrollo adecuado del proceso penal, lo que se evidencia en la configuración jurídica del delito, la correcta determinación de responsabilidad y el ejercicio de las garantías del debido proceso en cumplimiento de los principios del proceso penal. Una adecuada imputación evita interpretaciones extensivas y que el delito no sea erróneamente confundido con el hurto o la estafa.
Keywords: DELITO; PROCESO PENAL; ROBO; IMPUTACION